2010
DOI: 10.1080/10447310903498825
|View full text |Cite
|
Sign up to set email alerts
|

Designing an Information Visualization Tool for Sensemaking

Abstract: The study presents the AVALANCHE visualization test-bed for sensemaking in illstructured problem domains. AVALANCHE allows the users to develop and frame hypotheses, analyze the hypotheses in the experimental domain, and provide cases for simulation experiments. The visualization and sensemaking support module in AVALANCHE provides human-computer interface and visualization supports. Validation experiments using groups aided with visualization and support tools and groups with no aiding was performed on two op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Similarly, the Entity Workspace provides an evidence panel for analysis to place relevant documents and generate hypotheses (Billman & Bier, 2007), whilst Dynapad offers a workspace for spatially organising personal document collections (Bauer, Fastrez, & Hollan, 2005). Finally, the S3 system embeds cognition into a visual interface for developing and analysing hypotheses (Ntuen, Park, & Gwang-Myung, 2010).…”
mentioning
confidence: 99%
“…Similarly, the Entity Workspace provides an evidence panel for analysis to place relevant documents and generate hypotheses (Billman & Bier, 2007), whilst Dynapad offers a workspace for spatially organising personal document collections (Bauer, Fastrez, & Hollan, 2005). Finally, the S3 system embeds cognition into a visual interface for developing and analysing hypotheses (Ntuen, Park, & Gwang-Myung, 2010).…”
mentioning
confidence: 99%
“…Several frameworks have been suggested to explain why visual representation could enhance performance (Jun, Landry, & Salvendy, 2011;Ntuen, Park, & Gwang-Myung, 2010). However, studies comparing graphs and tables reported mixed results: Some reported that graphs are better than tables, but the others reported opposite results.…”
Section: Evaluation Of Tabular Visualizationsmentioning
confidence: 87%
“…Joint cognitive systems are widely used in the support of performing complex tasks including air traffic control (e.g. Harris 2013;Hollnagel 2007), emergency and crisis management (e.g., Furniss and Blanford, 2006;Ntuen et al, 2006), warehouse management (Accorsi, Manzini, and Maranesi, 2013), and policy making (Ntuen, Park, and Gwang-Myung, 2010;Parsons and Sedig, 2014). Our results also suggest that joint cognitive systems may be insufficient for human users to develop a good internal representation of a complex situation.…”
Section: Discussionmentioning
confidence: 99%